2020
DOI: 10.3390/jcm9061817
|View full text |Cite
|
Sign up to set email alerts
|

Increased Acid-Producing Diet and Past Smoking Intensity Are Associated with Worse Prognoses among Breast Cancer Survivors: A Prospective Cohort Study

Abstract: Current dietary guidelines do not consider cancer survivors’ and past smokers’ low capacity to regulate their acid–base balance. People with a low capacity to regulate their acid–base balance are more susceptible to acid-producing diets. We studied a cohort of 2950 early stage breast cancer survivors who provided dietary information at baseline and during follow-up. We assessed the intakes of acid-producing diets via two commonly used dietary acid load scores: potential renal acid load (PRAL) and net endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 61 publications
0
39
0
Order By: Relevance
“…For instance, we previously demonstrated that past smokers with higher past smoking intensity (pack-years ≥ 15) had different susceptibility to an acid-producing diet than never smokers and past smokers with a lower past smoking intensity [50]. Our previous paper [50] and the current paper both suggest that we need to consider the impacts of foods in the context of who will consume the diets; in other words, the impacts of foods will be different among people with different smoking statuses. Furthermore, we focused on red meat instead of other types of meat because it is one of the most important and controversial topics.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we previously demonstrated that past smokers with higher past smoking intensity (pack-years ≥ 15) had different susceptibility to an acid-producing diet than never smokers and past smokers with a lower past smoking intensity [50]. Our previous paper [50] and the current paper both suggest that we need to consider the impacts of foods in the context of who will consume the diets; in other words, the impacts of foods will be different among people with different smoking statuses. Furthermore, we focused on red meat instead of other types of meat because it is one of the most important and controversial topics.…”
Section: Discussionmentioning
confidence: 99%
“…Only participants that were not undergoing chemotherapy, had no evidence of recurrence or metastasis, and had no other cancer within the past 10 years except nonmelanoma skin cancer or carcinoma in situ of the cervix were enrolled. Further details of the original WHEL study can be found in previous studies [ 13 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In today’s world, western diets consist of high acid-producing foods, such as unprocessed and processed meat, and low alkaline-producing foods, such as fruit and vegetables. Although some studies have reported that higher consumption of alkaline foods was associated with increased lifespan [ 12 ] and increased acid-producing diets were associated with increased mortality [ 13 ], results on alkaline diets and physical health are inconsistent. A randomized trial has shown that a vegetarian diet leads to greater improvement in physical and mental health among individuals with diabetes [ 14 ], whereas another cross-sectional study reported that a vegetarian diet was associated with poor mental health but no difference in physical health among vegetarians and semi-vegetarian women compared to non-vegetarians [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Covariates were identified a priori based on previous studies of DAL and breast cancer incidence/mortality [ 6 , 16 , 32 ], and using directed acyclic graphs. The covariates were included in our multivariable regression models to control for confounding of the association between DAL and mortality following breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…As such, dietary acid load (DAL) is estimated in epidemiologic studies using food frequency questionnaires (FFQs) [ 11 ]. Results from studies of the association between FFQ-estimated DAL and risk of incident breast cancer have been mixed [ 12 , 13 , 14 , 15 ] and, to date, only one study has examined DAL in association with mortality following breast cancer [ 16 ]. In that study, the rates of all-cause and breast cancer mortality were elevated 54% and 52%, respectively, for the highest versus the lowest quartiles of NEAP, and associations were stronger among smokers with over 15 pack-years [ 16 ].…”
Section: Introductionmentioning
confidence: 99%